Using Expressive Writing in Group Counselling to Reduce Insecure Behaviour Among Fatherless Students - Nadia Latifatma; Yenti Arsini (MASI Mandiri Edukasi, 2025)
Adolescence is a critical phase in identity formation, which is strongly influenced by interpersonal interactions, including relationships with parents. The absence of a father figure can lead to emotional and social voids in adolescents, often resulting in feelings of worthlessness and the emergence of insecure behaviour. To evaluate the effectiveness of expressive writing in group counselling for reducing insecure behaviour among fatherless students in Grade 10 Computer and Network Engineering students at SMK Mandiri. This research employed a quantitative method with a pre-experimental one-group Pre-Test and post-test design and a purposive sampling technique. A total of 8 fatherless students who exhibited high levels of insecurity were selected as participants. Data were collected using validated fatherless and insecure behaviour scales. The results of the study, based on the paired sample t-test analysis, showed a significant value for Sig. (2-tailed) = 0.000 < 0.05. These findings indicate that the expressive writing technique in group counselling is effective in reducing insecure behaviour among fatherless students.